Head-to-head comparison of [18F]-fluorodeoxyglucose and [18F]-fluorocholine positron emission tomography/computed tomography in three patients with rare gestational trophoblastic neoplasms: A case series - Tanyaluck Thientunyakit; Thonnapong Thongpraparn; Tossaporn Siriprapa; Juri G. Gelovani (World Journal of Nuclear Medicine)
We report the efficacy of dual positron emission tomography/computed tomography (PET/CT) imaging with [18F]-2'-fluoro-2'-deoxy-D-glucose ([18F]-FDG) and [18F]-fluorocholine ([18F]-FCH) in patients with gestational trophoblastic neoplasia (GTN) for primary diagnosis and staging of this rare pregnancy-related disorder. Whole-body PET/CT with [18F]-FDG and [18F]-FCH was performed in three patients with GTN in 2 consecutive days. Each detectable lesion was characterized by visual and quantitative analyses. As compared to CT alone, PET/CT with [18F]-FDG and [18F]-FCH PET/CT revealed more hypermetabolic metastatic lesions in the body, but not in the brain. The standard uptake value of [18F]-FDG was generally higher than [18F]-FCH in all detectable tumor lesions. In conclusion, both [18F]-FDG and [18F]-FCH PET/CT can be used for diagnosis and staging for GTN, based on their sensitivity for small extracerebral metastatic lesions. Additional studies are warranted to determine whether the PET/CT imaging with [18F]-FDG and [18F]-FCH can serve as a biomarker of GTN aggressiveness, for prediction of treatment response.